PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN DAN EFEKTIVITAS SISTEM PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (STUDI PADA WAJIB PAJAK ORANG PRIBADI YANG TERDAFTAR DI KANTOR PELAYANAN PAJAK PRATAMA BANDA ACEH) - Wulandara, Intan Kartika; adnan, adnan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
The purpose of this research is to examine the effect of modernization of system administration tax and taxation system effectiveness on taxpayer compliance. The type of data used in primary data which collected from questionnaires. Samples are chosen using the purposive sampling method. In which consist of 100 individual taxpayer who have a job as entrepreneurial business such as trade, business services and business industry listed in KPP Pratama Banda Aceh. The analysis technique used multiple linear regression using SPSS 21. This research uses modernization of system administration and taxation system effectiveness as independent variable, while the dependent variable is taxpayer compliance. According to the simultaneous test (F-test), the results shows that modernization of system administration tax and taxation system effectiveness significantly affect the taxpayer compliance. According to the partial test (t-test) all independent variable significantly affect the taxpayer compliance.